2008
DOI: 10.1542/peds.2007-2312
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians’ Description of Factors Influencing Their Reporting of Suspected Child Abuse: Report of the Child Abuse Reporting Experience Study Research Group

Abstract: Decisions about reporting to child protective services are guided by injury circumstances and history, knowledge of and experiences with the family, consultation with others, and previous experiences with child protective services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
145
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(154 citation statements)
references
References 10 publications
5
145
0
4
Order By: Relevance
“…This study indicates that decisions to report suspicious injuries were less tied to definitions, statistics, and reporting laws than to a variety of factors related to patient-physician relationships and experiences with CPS [4,5].…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…This study indicates that decisions to report suspicious injuries were less tied to definitions, statistics, and reporting laws than to a variety of factors related to patient-physician relationships and experiences with CPS [4,5].…”
mentioning
confidence: 87%
“…A 2008 study found that pediatricians in an office-based setting do not always report suspicious injuries [4,5]. Physicians from two national pediatric practice-based research networks were recruited and 434 reported information from more than 15,000 injuries seen in their offices.…”
mentioning
confidence: 99%
“…Also, when reports are made to law enforcement rather than, or in addition to, child welfare, the law enforcement agencies may be similarly ill-prepared to connect trafficking victims and survivors to the most appropriate services. These factors have contributed to reluctance on the part of some health care and other professionals to submit mandated reports [27][28][29].…”
Section: Incorporating Trafficking Into Mandatory Child Abuse Reportimentioning
confidence: 99%
“…In both Jones et al (2008) and Flaherty et al (2006) the researchers found that physicians saw previous history with the family and their own experiences in working with child protective services as key factors influencing their decision-making processes in the intentionally ambiguous vignettes posited by the researchers. The introduction of history with the family into the situation makes the replicability of the data difficult because the history of particular subjects will trump other factors.…”
Section: Characteristics That Influence Reporting Decisionsmentioning
confidence: 99%